Pembinaan Dan Pelatihan Pelaporan Keuangan di SMK Batam Business School - Harahap, Baru; Rahmat, Muhammad (LPPM Universitas Putera Batam, 2024)
This community service project highlights the importance of implementing an effective financial reporting system at SMK Batam Business School to ensure transparency, accuracy, and financial sustainability. Through an assessment of efforts to improve financial management, the study found that SMK Batam Business School has taken significant steps such as staff training, the implementation of modern accounting software, and improving understanding of applicable accounting standards. In addition, the school has enhanced its financial reporting processes by preparing regular financial statements and closely monitoring the budget. These efforts have ultimately strengthened financial management, improved the accuracy of financial information, and increased transparency and accountability. This study provides valuable insights for other educational institutions seeking to improve their financial management systems.